On the journey of reconciliation: the university archivist as guide, guardian and muse. Issue 1 (January 2020) - Gorder, Erika B.
Abstract : Its recently celebrated 250th anniversary (2015–2016) provided Rutgers University with an opportunity for critical and inclusive examination of its past, particularly the role of slavery and institutionalized racism in its development. Inspired by the Black Lives Matter movement and the investigations of slavery initiated by the colonial colleges in the United States of America, Rutgers wanted to ensure that the enslaved, hidden and ignored people of our past are acknowledged and heard. It established the Committee on Enslaved and Disenfranchised Populations in Rutgers History which recognized that extensive archival inquiry was required to bring these histories to light. Collaborative research resulted in the three-volume scholarly work beginning with Scarlet and Black. Vol. I: Slavery and Dispossession in Rutgers History that offers inspiration for other projects utilizing university archives resources. These initiatives reveal voices from the past, but they have also given voice and recognition to the archives itself. As institutions recount their histories, the narratives illustrate the multiple uses of history and memory in institutional culture. At the centre of this historical work stands the archives but more importantly the archivist, a key figure with many roles: editor, writer, curator, researcher, translator, guardian and champion. Archivists of higher education are active participants in both traditional scholarship and collaborative approaches to historical analysis and shape the narratives of their institutions. Beyond the physical space and records themselves, the university archives can play a vibrant role in institutional life and are critical to the success of the multi-faceted mission of higher education.